2016
DOI: 10.1016/j.rpor.2016.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic aspects of skull base tumors

Abstract: Skull base tumors form a highly heterogeneous group. As there are several structures in this anatomical site, a large number of different primary malignancies might develop, as well as a variety of secondary (metastatic) tumors. In this article, the most common malignancies are presented, along with a short histopathologic description. For some entities, an immunohistochemical profile is also given that should be helpful in proper diagnosis. As many pathologic diagnoses nowadays also include genetic studies, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The World Health Organization (WHO) classifies them as grade I tumors due to their lack of histological signs of malignancy [3], although malignant transformation has been reported in rare cases [4]. Histologically, there are two main CP subtypes, namely, adamantinomatous and papillary, which differ in age distribution, frequency, biology, and clinical outcome [2,[5][6][7]. Adamantinomatous CP predominantly affects subjects younger than 14 years of age and is, therefore, considered the "pediatric" type, accounting for 5-10% of central nervous system (CNS) tumors in this age group [5,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The World Health Organization (WHO) classifies them as grade I tumors due to their lack of histological signs of malignancy [3], although malignant transformation has been reported in rare cases [4]. Histologically, there are two main CP subtypes, namely, adamantinomatous and papillary, which differ in age distribution, frequency, biology, and clinical outcome [2,[5][6][7]. Adamantinomatous CP predominantly affects subjects younger than 14 years of age and is, therefore, considered the "pediatric" type, accounting for 5-10% of central nervous system (CNS) tumors in this age group [5,7].…”
Section: Introductionmentioning
confidence: 99%
“…Histologically, there are two main CP subtypes, namely, adamantinomatous and papillary, which differ in age distribution, frequency, biology, and clinical outcome [2,[5][6][7]. Adamantinomatous CP predominantly affects subjects younger than 14 years of age and is, therefore, considered the "pediatric" type, accounting for 5-10% of central nervous system (CNS) tumors in this age group [5,7].…”
Section: Introductionmentioning
confidence: 99%
“…The treatment and the prognosis may dramatically change in the case of a benign lesion without compression of critical structures or a malignant tumour invading and infiltrating nervous tissue in the brainstem or in the temporal lobes. A comprehensive review of the main tumour types arising in the skull base is reported by Marszalek et al 3 who describe the main pathologic features of these tumours. The correct histological diagnosis is the first step for planning the subsequent imaging staging and discuss possible treatment approaches.…”
mentioning
confidence: 99%